Genetic ancestry concordant RNA splicing in prostate cancer involves oncogenic genes and associates with recurrence - Muthana Al Abo; Wen-Chi Foo; Lauren E. Howard; Shannon McGue; Bonnie Lacroix; Julie Kephart; Angela Clayton; Blair Thornburg; Monika Anand; Michael B. Rothberg; Shannon J. McCall; Jiaoti Huang; et al. (npj Precision Oncology)
Abstract Black men suffer disproportionately from prostate cancer (PCa) compared to men of other races and ethnicities. Comparing the molecular landscape of PCa among Black and White patients has the potential to identify targets for development of new precision medicine interventions. Herein, we conducted transcriptomic analysis of prostate tumors and paired tumor-adjacent normals from self-reported Black and White PCa patients and estimated patient genetic ancestry. Clinical follow-up revealed increased biochemical recurrence (BCR) among Black patients compared to White patients with high-grade PCa. Transcriptomic analysis identified differential alternative RNA splicing events (ARSs) between Black and White PCa patients. Genes undergoing genetic ancestry-concordant ARSs in high-grade or low-grade tumors involved cancer promoting genes. Most genes undergoing genetic ancestry-concordant ARSs did not exhibit differential aggregate gene expression or alternative polyadenylation. A number of the genetic ancestry-concordant ARSs associated with BCR; thus, genetic ancestry-concordant RNA splice variants may represent unique targets for PCa precision oncology.